Mesoporous WO3 Nanofibers With Crystalline Framework for High-Performance Acetone Sensing - Xu, Haiyun; Gao, Jie; Li, Minhan; Zhao, Yuye; Zhang, Ming; Zhao, Tao; Wang, Lianjun; Jiang, Wan; Zhu, Guanjia; Qian, Xiaoyong; Fan, Yuchi; Yang, Jianping; et al. (Frontiers in Chemistry, 2019)
Semiconducting metal oxides with abundant active sites are regarded as promising candidates for environmental monitoring and breath analysis because of their excellent gas sensing performance and stability. Herein, mesoporous WO3 nanofibers with crystalline framework and uniform pore size is successfully synthesized in aqueous phase via electrospinning method with ammonium metatungstate as tungsten sources, SiO2 nanoparticles and polyvinylpyrrolidone as sacrificial templates. The obtained mesoporous WO3 nanofibers exhibit controllable pore size of 26.3-42.2 nm, specific surface area of 24.1-34.4 m2g−1, pore volume of 0.15-0.24 cm3g−1. The unique hierarchical structure with uniform mesopores and interconnected channels could facilitate the diffusion and transportation of gas molecules in the framework. Gas sensor based on the mesoporous WO3 nanofibers exhibits an excellent performance in acetone sensing with a low limit of detection (<1 ppm), short response-recovery time (24 s/27 s), a linear relationship in a broad range, and good selectivity.